Pengaruh Model Pembelajaran Creative Problem Solving (CPS) pada Kemampuan Berpikir Kreatif Siswa Sekolah Dasar - Putri, Nadila; Jannah, Miftahul; Dianri, Adillah; Riani, Elsa; Ernita, Reza; Wulandari, Citra; Nurhaswinda, Nurhaswinda (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2023)
This This research was motivated by the low creative thinking skills of class V students at SDN 005 Bukit Ranah. One solution to overcome this problem is to use the creative problem solving (CPS) model. The research aims to determine whether or not there is an influence of the creative problem solving (CPS) learning model on the creative thinking skills of class V students at SDN 005 Bukit Ranah. This research is a research. The research design used in the research is a quasi-experiment (Quasi Experiment) in the form of a nonequivalent control group design. The population in this study was all class V students at SDN 005 Bukit Ranah, totaling 70 students. In this research, there are classes VA and VB, where class VA is the Experiment class and class V is the Control class. The results of the hypothesis test using the one way anova test with a significance level of 0.05 obtained a sig (2-tailed) (0.034) < Î± (0.050) value so it can be said that the two classes have a significant difference. Based on the data analysis, it can be concluded that there is an influence between the creative problem solving (CPS) learning model on the creative thinking skills of class VA students in the experimental class and students who use conventional learning in class VB students at SDN 005 Bukit Ranah. Keywords: Creative Problem Solving (CPS) Model, Creative Thinking Skills and Elementary School Students.